2020
DOI: 10.1109/access.2020.2964050
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness Assessment of Massage Therapy Using Entropy-Based EEG Features Among Lumbar Disc Herniation Patients Comparing With Healthy Controls

Abstract: Massage therapy (MT) is a useful complementary and alternative therapy widely used in treating low back pain (LBP), including lumbar disc herniation (LDH). However, few studies revealed the quantitative entropy-based features of electroencephalography (EEG) for the MT effectiveness for the LDH patients. This study investigated the immediate effects of Chinese massage on four EEG rhythms, using the eight entropy-based features (approximation entropy (ApEn), Sample Entropy (SampEn), wavelet entropy (WaveEn), Hil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 72 publications
(106 reference statements)
1
5
0
Order By: Relevance
“…Vatankhah et al found that no-pain and cold thermal pain classification accuracy was 14% higher using approximate entropy vs. spectral features ( 54 ). The superior classification accuracy of entropy-based features aligns with our results, as well as other studies demonstrating changes in PE outcomes in relation to pain ( 60 , 61 ). Our study also aligns with prior CPT studies reporting changes in theta activity in relation to pain stimulation ( 27 , 28 , 30 ).…”
Section: Discussionsupporting
confidence: 91%
“…Vatankhah et al found that no-pain and cold thermal pain classification accuracy was 14% higher using approximate entropy vs. spectral features ( 54 ). The superior classification accuracy of entropy-based features aligns with our results, as well as other studies demonstrating changes in PE outcomes in relation to pain ( 60 , 61 ). Our study also aligns with prior CPT studies reporting changes in theta activity in relation to pain stimulation ( 27 , 28 , 30 ).…”
Section: Discussionsupporting
confidence: 91%
“…With the development of economy, the progress of society and the change of people's life and work style, the age of onset of the disease is becoming younger and younger [ 6 ]. Li et al believe that due to its long course and easy repetition, it seriously affects the daily life and work of LDH patients, brings huge pain and certain economic burden to patients, and also causes psychological and mental pressure to patients [ 7 ]. Hu et al found that the basic pathological factor of LDH is the imbalance between inorganic and organic components in the intervertebral disc, and the acute and chronic injury of the waist, the increase of intervertebral disc pressure caused by long-term fixed sitting posture, lumbar puncture, genetics, age, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Entropy is a nonlinear dynamical index [17,18] that has been widely used in recent years for various applications including ship-radiated noise feature extraction, by virtue of its ability to provide a measure of the uncertainty and irregularity of nonlinear signals [19][20][21][22][23][24], and many scholars have improved entropy in various aspects in order to improve its performance. In 2002, Bandt and Pompe [25] proposed the concept of permutation entropy (PE) for describing the complexity of time series and chaotic dynamical systems, which is also widely used in various types of hydroacoustic signal feature extraction due to its simpler algorithm, faster computation, and better noise immunity.…”
Section: Introductionmentioning
confidence: 99%